Spontaneous Lumbar Curve Correction Following Vertebral Body Tethering of Main Thoracic Curves. (21st September 2022) - Catanzano, Anthony A.; Newton, Peter O.; Bastrom, Tracey P.; Bartley, Carrie E.; Parent, Stefan; Miyanji, Firoz; Hoernschemeyer, Daniel G.; Alanay, Ahmet; Blakemore, Laurel; Neal, Kevin; Lonner, Baron; Haber, Lawrence; et al.
Abstract : Background: Growth modulation through anterior vertebral body tethering (AVBT) has emerged as a fusionless option for the treatment of progressive scoliosis. When tethering the main thoracic curve, the compensatory thoracolumbar/lumbar curve must correct indirectly as a result. The present study evaluated the response of these lumbar curves following AVBT of the main thoracic curves. Methods: Patients who underwent thoracic AVBT and who had a minimum follow-up of 2 years were included. Magnitudes of the thoracic and lumbar curves were recorded preoperatively and at the first-erect and 2-year postoperative visits. Lumbar curves were further stratified according to their lumbar modifier (A, B, or C). Analysis of variance (ANOVA) and repeated-measures ANOVA were performed to compare correction rates, and the Pearson coefficient was utilized to determine the correlation between the tethered thoracic curve and uninstrumented lumbar curve magnitudes. Results: A total of 218 patients were included. Thoracic curve correction was 40% at the first-erect visit and 43% at 2 years (p = 0.012). Lumbar correction was 30%, 26%, and 18% at the first-erect visit (p < 0.001 for all compared with preoperatively) and minimally changed at 31%, 26%, and 24% at 2 years for lumbar modifiers A, B, and C, respectively. A total of 118 patients (54%) showed thoracic curve improvement between the first-erect and 2-year visits. In a subgroup analysis, these patients had a correction in lumbar curve magnitude from preoperatively to the first-erect visit of 30%, 22%, and 16% for lumbar modifiers A, B, C, respectively, that increased to 42%, 34%, and 31% at 2 years, with strong correlation to thoracic correction at 2-year follow-up (r = 0.557, p < 0.001). Conclusions: Although there was immediate lumbar correction following AVBT of a main thoracic curve, further improvement following initial correction was only observed among patients with growth modulation of the thoracic curve. Considering all patients, the uninstrumented lumbar curve corrected 30% at 2 years and the instrumented thoracic curve corrected 40%. As indications for AVBT are refined, these data will provide insight into the response of the uninstrumented lumbar curve. Level of Evidence: Therapeutic Level III . See Instructions for Authors for a complete description of levels of evidence.